Evaluasi Keberhasilan Program Jaminan Kesehatan Bali Mandara (JKBM) : Studi Kasus di Puskesmas Sukawati II Kecamatan Sukawati Kabupaten Gianyar - Astriyani, Ida Ayu Desy; Marhaeni, A.A.I. Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 1, Januari 2013 (pp. 1-62), 2013)
Every country has the difference quality of human resources. Human resources are human capital that can be relied upon the value creation of sustainable competitive advantage. The quality of human resources is a process of improving the quality of human beings that have many options to improve their quality of life and level of welfare. Improvement of Human Development Index (IPM) particularly in Health, can be done by providing aid of health care programs that directed to the people to improve their health status. The first aim of this research is to know the successful of Bali Mandara Health Insurance Program (JKBM) that seen by input indicator, the process and output; second , to find out public perception about the service of Bali Mandara Health Insurance (JKBM); Third , to find out the benefits that received by users of Bali Mandara Health Insurance (JKBM). The Successful rate of Bali Mandara Health Insurance (JKBM) was considered by each indicator that used in this research. The respondent of this research are community of Bali Mandara Health Insurance (JKBM) user at Sukawati II Public Health Centre , Sukawati Sub-District,and Gianyar District, by the number of 99 people. The Method of sample determination is proportionate stratified random sampling. The method of Data collection that used are observation and interview by using the primary and secondary data. This research using two data analysis methods. First, Using the descriptive statistic methods to find out the success rate of program and to find out perception of people about Bali Mandara Health Insurance (JKBM). Second, Using of non-parametric statistic methods with McNemar’s Method to know the benefits of Bali Mandara Health Insurance (JKBM).  The samples that used in this research is about 99 (ninety-nine) respondents. The Result indicates the successful rate of  Bali Mandara Health Insurance (JKBM) and could seen by the input indicator, the process, and the successful output. It’s seen from the average scores that obtained from each of the input indicators, process and output. Perception of people who use Bali Mandara Health Insurance (JKBM) program at Sukawati II Public Health Centre , Sukawati Sub-District,and Gianyar District relatively success. It seen by the average answer score that obtain by respondents, because all of the indicator is above 3 Point. Bali Mandara Health Insurance (JKBM) program at Sukawati II Public Health Centre , Sukawati Sub-District,and Gianyar District provide positive benefits to all the people.
Keywords: evaluation; health; insurance